Galactose-binding lectin from the seeds of champedak (Artocarpus integer): sequences of its subunits and interactions with human serum O-glycosylated glycoproteins - Rahman, M.A.; Karsani, S.A.; Othman, L.; Rahman, P.S.A.; Hashim, Onn Haji (2002)
Our group has previously reported the isolation, partial characterisation, and application of a Galbeta1-3GalNAc- and IgA1-reactive lectin from the seeds of champedak (Artocarpus integer). In the present study, we have subjected the purified lectin to reverse-phase high performance liquid chromatography and sequenced its subunits. Determination of the N-terminal sequence of the first 47 residues of the large subunit demonstrated at least 95 homology to the N-terminal sequence of the alpha chains of a few other galactose-binding Artocarpus lectins, The two smaller subunits of the lectin, each comprised of 21 amino acid residues, demonstrated minor sequence variability. Their sequences were generally comparable to the beta chains of the other galactose-binding Artocarpus lectins. When used to probe human serum glycopeptides that were separated by two-dimensional gel electrophoresis, the lectin demonstrated strong apparent interactions with glycopeptides of IgA1, hemopexin, alpha(2)-HS glycoprotein, alpha(1)-antichymotrypsin, and a few unknown glycoproteins. Immobilisation of the lectin to Sepharose generated an affinity column that may be used to isolate the O-glycosylated serum glycoproteins. (C) 2002 Elsevier Science (USA). All rights reserved.